Viscoelastic characteristics of carbon fiber-reinforced epoxy filament wound laminates - Ornaghi Jr, Heitor L.; Neves, Roberta M.; Monticeli, Francisco M. [UNESP]; Almeida, Jose Humberto S. (Elsevier B.V., 2020)
The mechanical properties of fiber-reinforced composites are time-dependent due to the viscoelastic nature of polymers. This study covers the creep/recovery and dynamic mechanical properties of high-performance composites under low-stress loading. Flat unidirectional 6-layer laminates are manufactured by dry-filament winding and cured under hot compression. Four different laminates are studied: [0](6), [30](6), [60](6), and [90](6). Dynamic mechanical curves and creep behavior are highly dependent on the ply angle up to 60 degrees. The fiber orientation does not influence significantly the glass transition temperature, except for the [0](6) laminate, which has a higher T-g compared to the other samples. Normalized dynamic mechanical curves are plotted aiming to study the behavior of the material passing through the glass transition temperature (T-g). The modulus decreases for fiber angles toward the transverse direction, but the energy dissipation occurs in a broader temperature range. Creep/recovery also demonstrates a dependency on the fiber orientation, in which the sample [0](6) (highest storage modulus) has the lowest strain, leading to higher molecular hindrance compared to the other laminates.
Keywords: Creep; Recovery; Viscoelasticity; Filament winding